2021
DOI: 10.1515/nanoph-2021-0276
|View full text |Cite
|
Sign up to set email alerts
|

Onset of charge interaction in strong-field photoemission from nanometric needle tips

Abstract: Strong-field photoemission from nanostructures and the associated temporally modulated currents play a key role in the development of ultrafast vacuum optoelectronics. Optical light fields could push their operation bandwidth into the petahertz domain. A critical aspect of their functionality in the context of applications is the impact of charge interaction effects. Here, we investigated the photoemission and photocurrents from nanometric tungsten needle tips exposed to carrier-envelope phase (CEP)-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…16 In work focusing on strong field emission, it has recently been shown that multielectron effects strongly affect the resulting electron spectra during the emission process. 17 Great progress has also been made on Coulomb interactions in electron emission in theory and simulations: Resolution limits for ultrafast electron diffraction 18 or aberrations caused by space charge in a TEM 19 per pulse, single-trajectory simulations were carried out, showing how Coulomb interactions can limit the brightness of cold field emission 20 and pulsed electron emission. 21 As we pointed out, the focusability of an electron beam is closely connected to its effective source size, a quantity which in turn is associated with spatial coherence.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 In work focusing on strong field emission, it has recently been shown that multielectron effects strongly affect the resulting electron spectra during the emission process. 17 Great progress has also been made on Coulomb interactions in electron emission in theory and simulations: Resolution limits for ultrafast electron diffraction 18 or aberrations caused by space charge in a TEM 19 per pulse, single-trajectory simulations were carried out, showing how Coulomb interactions can limit the brightness of cold field emission 20 and pulsed electron emission. 21 As we pointed out, the focusability of an electron beam is closely connected to its effective source size, a quantity which in turn is associated with spatial coherence.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This theoretical model has been applied to describing the strong-field ionization from nanospheres 111 and metal nanotips. 112 …”
Section: Ultrafast Molecular Dynamics In Nanosystemsmentioning
confidence: 99%
“…These effects can be accounted for in higher level descriptions such as the semi-classical Mie Mean-field Monte-Carlo (M 3 C) model [22,41,47] or via microscopic particle-in-cell (MicPic) models [62,63]. In the following, the details of M 3 C are discussed, as this method has been utilized in most of the scenarios presented in this review [41,43,44,[46][47][48]54,55,64] and was recently also extended for the description of strong-field ionization from metal nanotips [65].…”
Section: Theoretical Toolsmentioning
confidence: 99%
“…Although nanospheres will probably not be very suitable for future technical applications themselves, it is expected that many of the fundamental physical insights first obtained utilizing these simple model systems are also of major importance for more applications-relevant systems and application fields like sub-cycle laser processing or Petahertz optoelectronics employing other nanostructures such as nanotips [29]. For example, only recently the impact of charge interaction on the photoemission, first observed with dielectric nanospheres, has also been demonstrated with metal nanotips [65].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%